METHODOLOGY FOR IMPROVING PHYSICAL ENDURANCE IN FIELD HOCKEY (EXAMPLE OF GIRLS AGED 10–12) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes methodological approaches aimed at improving physical endurance in girls aged 10–12 engaged in field hockey. The research explores the growing popularity of field hockey among youth, the sport’s physical demands, and types of movements that require endurance, all studied on a scientific basis. Additionally, the article provides recommendations for developing an effective training system that takes into account the physiological characteristics of the young body. The results of the study are of practical value for coaches and specialists working with young athletes and contribute to the improvement of the training process in field hockey.